Pengaruh Umur Panen dan Jenis Legum Penutup Tanah terhadap Kualitas Tanah di Lahan Kering - ANTONIUS ALI; I GUSTI AYU MAS SRI AGUNG; GEDE WIJANA (Fakultas Pertanian Universitas Udayana, 2016)
Effects of Harvesting Time and Types of Legume Cover Crop on SoilQuality in Dryland Farming. Dryland is characterized by limited water resources, itdepends on amount and distribution of rainfall and its low quality of soil. Effort onimprovement of soil quality have been reported could be done through incorporating biomassof legume cover crops (LCC). Time of harvesting (then incorporated) and types of LCCdetermine the nutrients in the biomass, which finally affects the soil quality. A fieldexperiment was conducted to study the effects of time of harvesting and types of LCC on soilquality in dryland farming area in the village of Sengguan, Gianyar Regency, Bali Provincefrom August to December 2015. The experiment was arranged in a completely randomizedblock design with three replications. The treatments were the times of harvesting (or thenincorporation) (3, 6 and 9 weeks after sowing or WAS) was assigned as the first factor whiletypes of LCC (Mucuna pruriens L. (kara), Crotalaria juncea L.(orok-orok), and Phaseoluslunatus L. (kacang arbila)) as the second factor. Results of experiment indicated thatincorporated LCC biomass significantly (P<0.05) increased soil quality (physically,chemically and biologically). Mucuna pruriens and Phaseolus lunatus harvested and thenincorporated at 3 WAS significantly (P<0.05) increased chemical (organic-C, total-N,available K) quality of the soil, while when harvested 9 WAS the effects were moresignificant on physical (bulk density and porosity) quality. Soil moisture content increasedwhen Phaseolus lunatus was harvested and incorporated at 3 WAS, while microbial activities(indicated by soil respiration) increased when Mucuna pruriens was treated at the same time.